Устройство для защиты от замыканий на землю обмотки статора генератора - Шестакова В. В. Вера Васильевна; Вайнштейн Р. А. Роберт Александрович; Юдин С. М. Святослав Михайлович; Доронин А. В. Александр Викторович
опубл. 10.06.09